2018
DOI: 10.1053/j.ajkd.2017.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Kidney Function Decline in Autosomal Dominant Polycystic Kidney Disease: A Post Hoc Analysis From the HALT-PKD Trials

Abstract: Although many individuals with ADPKD have a linear decline in eGFR, prolonged intervals of stable GFRs occur in a substantial fraction. Lower body mass index was associated with more stable kidney function in early ADPKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 42 publications
0
36
0
Order By: Relevance
“…The rate of GFR decline in ADPKD has often been considered to have a "hockey stick" trajectory of conserved function followed by a period of rapid decline of 3-5 mL/ min/1.73 m 2 /y (22)(23)(24). This is partially reflected in recent analysis of the CRISP and HALT PKD populations (25,26). While mild groups had extended preserved function, steeper curvilinear slopes were associated with increasingly severe MICs, with close to a linear decline for MIC-1E.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of GFR decline in ADPKD has often been considered to have a "hockey stick" trajectory of conserved function followed by a period of rapid decline of 3-5 mL/ min/1.73 m 2 /y (22)(23)(24). This is partially reflected in recent analysis of the CRISP and HALT PKD populations (25,26). While mild groups had extended preserved function, steeper curvilinear slopes were associated with increasingly severe MICs, with close to a linear decline for MIC-1E.…”
Section: Introductionmentioning
confidence: 99%
“…This variability in risk for ESKD is likely due to the interaction of genic factors[ 3 ] with environmental variables[ 4 ] that alter the expressivity of the clinical phenotype[ 5 , 6 ]. Routine tests performed during the initial clinical evaluation of affected patients, such as estimated glomerular filtration rate (eGFR), lack sensitivity as prognostic markers in early disease[ 7 ], and other clinical information (such as family history of early-onset of ESKD) do not have precision[ 8 ]. The uncertainty in predicting renal prognosis causes tremendous anxiety to patients and their families[ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous periods of stability or increase in estimated glomerular filtration rate occur in a significant proportion of patients with ADPKD. 13 Mechanical cyst reduction strategies, such as cyst aspiration and sclerosis with ethanol or laparoscopic cyst decortication, have been used for decades in an effort to relieve the pain associated with large cysts and/or large kidneys, with success rates for pain relief varying from 25% to 100% and follow-up ranging from 12 months to more than 10 years. [14][15][16][17] Similarly, among the 41 patients in the present study who reported symptoms due to mass effect of the large kidneys, w70% experienced improvement in their symptoms.…”
mentioning
confidence: 99%
“…Spontaneous periods of stability or increase in estimated glomerular filtration rate occur in a significant proportion of patients with ADPKD. 13 …”
mentioning
confidence: 99%